Development of applications for mobile devices - Xiao, Huiyong (2015)
Health problems like chronic diseases become a big issue to people nowadays. Monitoring the chronic diseases daily or has frequently monitor is a good way to track health condition and can provide an alert to the patient when health condition is worsening. Traditionally, people use a paper system to record the vital sign reading, but it is an inefficient way as people find it troublesome to do it daily and keeping the record. As a result, Personal Health Profile application has become popular for the individual to monitor chronic diseases. Such application only allows user manually to enter reading for both free of charge and pay version of applications. The objective of this project is to design and develop a free of charge application for people. Overall, the application is able to receive data from a health device with Bluetooth enabled. Next, the application is also able to support multiple users, multiple chronic disease monitoring using a line chart and multiple languages. Follow by, the application also lets the user manage their data and user account. Lastly, the application is simple, interactive and error free to use. Overall, the application was developed in Android, Java language using the Eclipse Software Development Kit.